Assessment of 4C Softskills Characteristics in Learning Productive Graphic Design Subject for Vocational School - Purnawirawan, Okta; Sudana, I Made; Harlanu, Muhammad (Journal of Vocational and Career Education, 2019)
The number unemployment of productive working age from Vocational High Schools (SMK) is in the top rank of 9.27% of 131.55 million people in the workforce. This happens because learning process focuses on teaching hard skills and ignores soft skills so that it causes the low absorption of graduates in the world of work. At the moment the quality of the learning assessment instrument in Vocational Schools is still considered to be invalid so that it has not been able to evaluate aspects that are evaluated in full in relation to soft skills. This study aims to develop 4C assessment instruments in productive learning of graphic design. Research and Development methods are applied in this research to produce assessment products in the form of tests and non-tests. This research produces an assessment instrument in the form of a test used to measure the cognitive domain (knowledge) while the non-test / performance (performance test) is used to measure the affective domain (attitude) and psychomotor (skills). The instrument has: (1) A validity level of 95%; (2) Effectiveness 81%; (3) Consistency level of 0.62; and (4) Reliability Level 0.875. This assessment instrument can be used by teachers in productive learning graphic design so that it can help in the assessment process.